Inyiak Upiak Palatiang - Pardi, Ari; Martarosa, Martarosa; Rafilosa, Rafilosa (Jurnal Seni, Desain dan Budaya)
Abstract? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ? ??Inyiak Upiak Palatiang was born in 1900s in Kubu Gadang Hamlet, Nagari Gunuang, Padang Panjang City, he is famous as a pandeka (swordsman) Minangkabau silat girl who controls the flow of silek gunuang (Silat Gunung). (Interview with grandson Inyiak Upiak Palatiang, Fardizal, 20.00WIB, Padang Panjang, January 8, 2017). Inyiak Upiak Palatiang is a Minangkabau martial arts master, when he is 100 years old, he is still active in preserving and preserving the art of Minangkabau culture, even being a teacher of silek tuo (old martial arts), He is also known as a reliable kicker with various dendang creations besides Inyiak Upiak Palatiang also likes to play art Randai tradition. Based on the explanation of the greatness of Inyiak Upiak Palatiang, pengkarya plans to lift it into a musical masterpiece of the archipelago that will be titled "Inyak Upiak Palatiang", with the reason of the name of Inyiak Upiak Palatiang already representing what he cared for during his life. Background of the phenomenon that has been described, it can be formulated a formulation of the creation of the work, that is how to transform the phenomenon of a female character Inyiak Upiak Palatiang , into a musical composition of the archipelago, which will be divided into two sub-works, namely Upiak and Palatiang.Keywords : Inyiak Upiak Palatiang, Women and MaestroAbstrakInyiak Upiak Palatiang lahir pada tahun 1900-an di Dusun Kubu Gadang, Nagari Gunuang, Kota Padang Panjang ,beliau terkenal sebagai? seorang pandeka (pendekar) perempuan silat Minangkabau yang menguasai aliran silek gunuang (Silat Gunung). (Wawancara dengan cucu Inyiak Upiak Palatiang, Fardizal, 20.00WIB, Padang Panjang, 8 Januari 2017). Inyiak Upiak Palatiang adalah seorang maestro silat Minangkabau, disaat umur beliau 100 tahun, beliau masih aktif dalam menjaga dan melestarikan seni budaya Minangkabau, bahkan menjadi seorang guru silek tuo (silat tua), beliau juga dikenal sebagai seorang pendendang yang handal dengan berbagai dendang ciptaannya selain itu Inyiak Upiak Palatiang juga gemar bermain kesenian tradisi Randai.Berlatar belakang dari fenomena tersebut, menjadi ketertarikan bagi pengkarya untuk penciptaan karya musik, yaitu mentranformasikan fenomena seorang tokoh perempuan Inyiak Upiak Palatiang, kedalam sebuah bentuk komposisi musik nusantara, yang akan dibagi menjadi dua sub bagian karya, yaitu Upiak dan Palatiang.Kata kunci : Inyiak Upiak Palatiang, Perempuan dan Maestro